Effect of Virgin Coconut Oil Application on the Skin of Preterm Newborns: A Randomized Controlled Trial. (29th June 2019) - Konar, Mithun Chandra; Islam, Kamirul; Roy, Atanu; Ghosh, Taraknath
Abstract: Background: Preterm constitutes a major part of neonatal mortality, particularly in India. Due to dermal immaturity, preterm neonates are susceptible to various complications like infection, hypothermia, etc. Emollient application is a traditional practice in our subcontinent. Aims: To find out the efficacy of coconut oil application for skin maturity, prevention of sepsis, hypothermia and apnea, its effect on long-term neurodevelopment and adverse effect of it, if any. Material and methods: A randomized controlled trial was conducted in the rural field practice area of Department of Community Medicine, Burdwan Medical College from March 2014 to August 2018. Preterm born in the study period was divided into Group A (received virgin coconut oil application) and Group B (received body massage without any application). Neonatal skin condition was assessed on 7th, 14th, 21st and 28th day of life. Neurodevelopmental status was assessed on 3rd, 6th and 12th months. Results: A total of 2294 preterm were included in the study. Groups A and B consisted of 1146 and 1148 preterm infants, consecutively. Mean gestational age of the study population was 31.9 ± 3.4 weeks and 50.4% were male. Mean weight loss in first few days was less in group A but mean weight gain per day was higher in group B. Lesser incidences of hypothermia and apnea, and better skin maturity and neurodevelopmental outcome were noted in group A. No significant adverse effect was noted with coconut oil application. Conclusion: Use of coconut oil helps in dermal maturity and better neurodevelopmental outcome. Further studies are warranted for universal recommendation.